Glutathione S-Transferase Activity in Wild Plants with 2, 4-Dichlorophenol (2, 4-DCP) Phytoremediation Potential. (11th February 2023) - Moharramzadeh, Mohammad; Ceylan, Zeynep; Atıcı, Ökkeş
Abstract: Glutathione S-transferases (GSTs) play important roles in many biochemical processes, including the detoxification of xenobiotics, herbicides and pesticides, as well as enhancing stress tolerance in plants. 2, 4-Dichlorophenol (2, 4-DCP), an extremely toxic chlorophenolic, is a pollutant used as raw material in many industries, including the production of most herbicides and insecticides. This study investigated the response of GST for the phytoremediation of 2, 4-DCP in Datura stramonium L., Amaranthus retroflexus L., and Sinapis arvensis L., plants with high phytoremediation potential following 2, 4-DCP application. The seedlings grown in a hydroponic system were exposed to various solutions of 2, 4-DCP in a concentration range from 75 to 275 ppm for 4 days. The GST activity was evaluated in the seedling roots and leaves. The activities in roots and leaves of D. stramonium increased to 125 ppm but decreased at 150 ppm and its higher doses compared to controls. In A. retroflexus, the GST activity increased to 175 ppm in leaves and 125 ppm in roots but decreased in both in parallel with higher doses of 2, 4-DCP. In S. arvensis, on the other hand, all doses of 2, 4-DCP decreased GST activity in leaves and roots compared to controls. Our results show that D. stramonium and A. retroflexus respond to 2, 4-DCP toxicity with high GST activity, whereas S. arvensis is able tolerate the same toxicity, possibly by a different mechanism.